Interarch relationship in complete bilateral cleft lip and palate using two surgical protocols for primary surgeries - Rufino, Shana dos Santos (2025)
Object: This study aimed to compare the dental arch relationship of patients with complete bilateral cleft lip and palate (BCLP) underwent 2 distinct primary surgery protocols. Material and Methods: The study sample included 66 patients with complete BCLP, aged from 6 to 9 years, who underwent cheiloplasty and palatoplasty in the first year of life. The Group 1 consisted of 33 patients (23 males and 10 females) with mean age of 7.85 years submitted to a single-stage palatoplasty from 12 to 36 months. The Group 2 comprised 33 patients (23 males and 10 females) with a mean age of 7.85 years who underwent a two-stage palatoplasty. Digital dental models were obtained for all patients during the mixed dentition, and the dental arch relationship was evaluated by 3 experienced orthodontists applying the BCLP yardstick. Intergroup comparisons were performed using the Chi-square, the Mann-Whitney U test or t test (P<0.05). Results: The mean occlusal index for the single-stage and two-stage groups were 2.88 and 2.67, respectively. There was no significant difference in the scores distribution between the two groups (P=0.467). Conclusion: The result from this study suggests that, in patients with complete BCLP, a similar interarch relationship is expected in the mixed dentition regardless of whether the palatoplasty was performed in one or two stages.